The Impact of Financial Crisis on Insurance Sector and the Regulatory Response - Nurul Syuhada, Zaidi; Nazaria, Md Aris; Suzila, Mohamed Yusof (Universiti Malaysia Sarawak (UNIMAS), 2018)
This paper aims to discuss what happen during the 2008 financial crisis and the reason behind it. This paper also aims to analyze the impact of the financial crisis to insurance sector and how they react. This paper also discussed the Solvency II (applied by the European Commission) as well as the Malaysian Risk-Based Capital. Lastly, this paper also provides some observation and suggestion on how similar crisis can be avoided in the future as well as ways to improve the regulations.